Impact of school gardens and complementary nutrition education in Burkina Faso. Issue 2 (3rd April 2019) - Schreinemachers, Pepijn; Ouedraogo, Mamounata Sandaogo; Diagbouga, Serge; Thiombiano, Amadou; Kouamé, Serge Rodrigue; Sobgui, Caroline Makamto; Chen, Hsiao-Pu; Yang, Ray-Yu
ABSTRACT: This study evaluates the combined impact of school vegetable gardens linked to complementary nutrition education on the nutritional awareness, knowledge, perceptions, and eating behavior of 8–14-year-old schoolchildren in Burkina Faso. The study uses a repeated cluster randomized controlled trial and a sample of 30 schools and 1, 760 schoolchildren. The results show a small but significant (p < 0.05) increase in knowledge of sustainable agriculture (+5.0%) and knowledge of food and nutrition (+6.6%), but no significant increase in other outcome indicators including fruit and vegetable consumption. More caution is needed in the promotion of school gardens for improving child nutrition in very low income countries.